PERANAN MODAL SOSIAL DALAM KEMENANGAN SATONO DARI JALUR INDEPENDEN PADA PEMILIHAN UMUM KEPALA DAERAH DI KABUPATEN LAMPUNG TIMUR TAHUN 2010 - I Gede Parguna Wisesa; Budi Setiyono; Susilo Utomo (Journal of Politic and Government Studies, 2014)
AbstractThis study analyzes the phenomenon of regional head candidates win elected throughindependent pathways in the election of regional heads in East Lampung District in the year2010, kadidat winner is elected to partner Satono-erwin that in fact they are a couple thatcarried through the non-party or often we call independent in the general election in 2010 alone,in Lampung, as many as 10 districts / cities in sequence hold pilbup / pilwali. The elections in2010 opened new opportunities for players who prefer to use an independent candidate when theimpenetrable political party lines as most political parties already have a candidate. What is thechance that an individual candidate or more popularly called "independents" that?In this study, researchers using a qualitative approach that will generate data descriptif. Thisstudy was conducted in East Lampung district, the data obtained through observation,interviews, the voting public, a successful team of camp Satono, local political observers, customshop seklaigus stores and religion, society, and some data obtained from documents related tothe topic this study.The strategy used in the election heads East Lampung district in 2010 that deliversSatono Erwin re-elected for the second time in the form of the election campaign, jejang career,mass mobilization, social capital, development and empowerment of communities throughprograms that pro-people and communication politics. Success in making the strategy deliver thecouple elected with less of the vote 237.251 or 47.72% of the vote to beat a couple YusranAmirullah Bambang Imam Santoso, S. Sos with the acquisition of 172.869 or 34.77% of the voteand couples Hi. Noverman Subing, SH,. MM and couples Ir. Hj. Citra Persada, M.ScYuliansyah, SH sound each earn 56.012 (11,27) voice and 31.027 (6,24).Keywords: social capital, regional head elections, independentBAB I PENDAHULUANDi tengah semakin kecewanya masyarakat banyak terhadap kiprah